Preservice Mathematics Teachers' Perceptions of School-Related Content Knowledge Tasks - Dian Permatasari; Tatang Herman (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2024)
School-related Content Knowledge (SRCK) encompasses profession-specific content knowledge essential for teaching secondary mathematics and bridging the gap between university and school mathematics. Preparing preservice teachers with this knowledge is vital for effective teaching. This study explores the perceptions and performance of preservice mathematics teachers regarding SRCK tasks. Using a qualitative approach and case study design, the research involved twenty third-semester preservice mathematics teachers selected through convenience sampling at a state university in Yogyakarta. Instruments included tests, questionnaires, and interviews to assess SRCK. Data analysis involved content analysis, inductive category formation, thematic categorization, and data triangulation. The findings reveal that preservice mathematics teachers consider SRCK tasks relevant and beneficial for their professional development. However, differences emerge in their evaluation of task relevance and realism, highlighting the need to incorporate more university-level mathematical concepts into SRCK tasks to bridge the gap between theory and practice. Despite recognizing the importance of university mathematics, there is a tendency to rely predominantly on school-level mathematics knowledge. This suggests that teacher preparation programs must address the challenge of mastering more complex university-level concepts to ensure that future educators are adequately prepared to teach advanced mathematical ideas. Varying levels of success in solving SRCK tasks underscore the necessity for a comprehensive integration of university-level mathematical concepts. Such integration aligns with efforts to enhance the relevance of university mathematics education for aspiring teachers. It is recommended that university mathematics be blended with school mathematics and future professional roles to improve conceptual understanding and teaching readiness.